Assessment of the integration of electric vehicles into the Colombian market by 2050 using system dynamics - Gálvez, Juan Camilo; Dyner, Isaac; Sanint, Enrique Ángel; Aristizábal, Andrés Julián (Institute of Advanced Engineering and Science, 2025)
This article focuses on evaluating the prospects and potential that Colombia possesses for achieving a complete transition to electric vehicles (EV), with the goal of reaching a 100% penetration of such vehicles by the year 2050. To address this challenge, four potential scenarios are proposed, each based on different approaches and strategies. To achieve the objective described in the article, a simulation modeling approach was employed. Through this process, a definitive model was obtained that enables a visual representation of the progress of the different scenarios over the years. This graphical representation offers a clear insight into which scenarios align with the established parameters to achieve the target of nearly 100% electric vehicle adoption in Colombia by 2050. Additionally, there is a considerable reduction in CO2 emissions produced by the transportation sector in Colombia, with a 27% decrease compared to 2023. This is noteworthy given that the number of vehicles in 2050 is expected to be significantly higher than in the initial period, thus beginning a phase of declining pollution in the country.